1997
DOI: 10.2116/analsci.13.supplement_493
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and Iron in the Finger and Foot Muscle from Blackfoot Disease Patients.

Abstract: Atomic absorption spectrophotometric method, for determination of arsenic and iron concentration in finger and foot muscles from Blackfoot Dim Patients(BFDPs), by amputation were developed. Thirty-four cases of BFDPs, at the most strict clinical examination and thirty cases of Non-BFDPs(NBFDPs) from the traffic accidents. NBFDPs from the same district were compared as the controls. Arsenic has been claimed to be major causative agents of Blackfoot Disease(BFD) in the south-western coast of Taiwan. We published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Accumulation of iron has been observed in various diseases including neurodegenerative disorder and cardiovascular disease (38 -42). A previous study indicated that the iron concentrations in muscles of finger and foot of patients with blackfoot disease were also about 2 times higher than that of non-blackfoot disease control (43). Pathological study also observed iron accumulation in the vascular wall of patients with blackfoot disease (Wang, unpublished data).…”
Section: Fig 3 (A)mentioning
confidence: 90%
“…Accumulation of iron has been observed in various diseases including neurodegenerative disorder and cardiovascular disease (38 -42). A previous study indicated that the iron concentrations in muscles of finger and foot of patients with blackfoot disease were also about 2 times higher than that of non-blackfoot disease control (43). Pathological study also observed iron accumulation in the vascular wall of patients with blackfoot disease (Wang, unpublished data).…”
Section: Fig 3 (A)mentioning
confidence: 90%
“…Sample pretreatment (19,22) Each 10±2 g of PDAT sample was washed carefully with 100 ml deionized water three times, in order to remove the outer trace elements. The samples were then put on filter paper to remove the deionized water for 10 minutes before digestion; 2±0.2 g (wet weight) of PDAT and 10 ml HNO 3 were added a digestion vessel.…”
Section: Confirmation Of Conditions Of Bfd Patients and Test Samplesmentioning
confidence: 99%
“…Analytical methods (19)(20)(21)(22) Atomic absorption spectrophotometer model Z-8200, (Hitachi Corp., Tokyo, Japan) was used. Flame atomic absorption spectrophotometer for iron and its accessory Hydride Forma-tion System HFS-2 also from Hitachi were used for determining arsenic and selenium.…”
Section: Apparatus and Chemical Reagentsmentioning
confidence: 99%
See 2 more Smart Citations